2021
DOI: 10.3390/metabo11040199
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Volatile Biomarkers for Bladder Cancer Detection and Staging through Urine Metabolomics

Abstract: Timely diagnosis is crucial to improve the long-term survival of bladder cancer (BC) patients. The discovery of new BC biomarkers based in urine analysis is very attractive because this biofluid is in direct contact with the inner bladder layer, in which most of the neoplasms develop, and is non-invasively collected. Hence, this work aimed to unveil alterations in the urinary volatile profile of patients diagnosed with BC compared with cancer-free individuals, as well as differences among patients diagnosed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
1
30
1
Order By: Relevance
“…S5), and the results showed that the correlation between age, gender, and BMI and the 27 differential metabolites were small (|r|≤0.3). Thus, it can be concluded that age, gender, and BMI in this study did not show a signi cant correlation with the changes in metabolites detected between bladder cancer patients and the cancer-free controls [3].…”
Section: Potential In Uence Of Age Gender and Bmi On Statistically Different Metabolite Levelscontrasting
confidence: 62%
See 1 more Smart Citation
“…S5), and the results showed that the correlation between age, gender, and BMI and the 27 differential metabolites were small (|r|≤0.3). Thus, it can be concluded that age, gender, and BMI in this study did not show a signi cant correlation with the changes in metabolites detected between bladder cancer patients and the cancer-free controls [3].…”
Section: Potential In Uence Of Age Gender and Bmi On Statistically Different Metabolite Levelscontrasting
confidence: 62%
“…Currently, screening for bladder cancer still relies heavily on invasive cystoscopy [2], which can directly show tumor lesions in the bladder, and can perform biopsies for further pathological examination. However, this uncomfortable procedure can lead to urethral injury, urinary tract infection, and hematuria [3]. On the other hand, urine cytology is a non-invasive method to detect cancer cells in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this may explain why the levels of (E)-hept-2-enal, (E)-2-hexenal, (E)-2-pentenal, (E)-2-octenal, and hexanal are reduced in the bile of tumor patients. These findings were consistent with some studies that volatile aldehydes are decreased in tumor cells ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 94%
“…Urine ketone is one of the routine urinalysis. Only a few studies reported an alteration of ketone in patients with bladder cancer in a metabolomics study [ 71 ]. However, ketone body in urine has been considered as a high correlation to diabetes [ 72 ].…”
Section: Discussionmentioning
confidence: 99%